Open Zenker’s Peroral Endoscopic Myotomy: A Comparative Analysis Of This Modified Technique Versus The Standard Zenker's Peroral Endoscopic Myotomy Approach - Bedi, Harjot Kaur; Fayyaz, Farimah; Almardini, Michel; Roshanshad, Romina; Khashab, Mouen A (Endoscopy)
Background and study aims Open Zenker’s peroral endoscopic myotomy (OZ-POEM) was developed to overcome clinical failures from persistent mucosal flap and difficult closure in Z-POEM. This study compares the outcomes of OZ-POEM and Z-POEM. Patients and Methods This retrospective study included consecutive patients who underwent Z-POEM (2/2020-12/2022) and OZ-POEM (1/2023-11/2024). The primary outcome was clinical success; secondary outcomes were technical success, adverse events, procedure time, and closure cost. Results Seventy-eight patients were included, 39 per group, with similar baseline characteristics. Clinical success was achieved in 94.8% and 97.4% of patients in the Z-POEM and OZ-POEM groups, respectively. Technical success was 100% in both groups. No clips (US $0) were used in the OZ-POEM, while a median of 6 clips were used in Z-POEM group (p<0.001), with a median cost of US$580 (IQR 485-758.75) (p<0.001). Median procedure time was shorter in the OZ-POEM group (21 minutes vs. 27 minutes, p=0.0007). One patient in each group suffered a severe AE that required repeat endoscopic intervention. Conclusions OZ-POEM demonstrates comparable clinical, technical and safety outcomes as Z-POEM, with significantly shorter procedural duration and closure cost. It simplifies Z-POEM technique, making it more scalable for trainees and therapeutic endoscopists.